2017
DOI: 10.1097/mpg.0000000000001685
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Portocholecystostomy

Abstract: In patients with biliary atresia with patent extrahepatic bile ducts, hepatoportocholecystomy is a good surgical technique that can prevent cholangitis. These results are counterbalanced by specific surgical complications that need to be known and looked for in the postoperative period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…But none has proven entirely satisfactory in terms of eliminating cholangitis. A retrospective study of 97 cases that underwent gallbladder Kasai from a single institution reported 46% of the patients to be jaundice free with their native liver after 5 years of follow-up ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…But none has proven entirely satisfactory in terms of eliminating cholangitis. A retrospective study of 97 cases that underwent gallbladder Kasai from a single institution reported 46% of the patients to be jaundice free with their native liver after 5 years of follow-up ( 7 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cholangiography is essentially redundant here, in that it will inevitably show a patent common bile duct into the duodenum but no sign of a more proximal biliary tree. Some centres, particularly in France, would consider a portocholecystostomy (i.e., the gallbladder opened and anastomosed to the transected portal plate) for BA to make use of this feature [ 20 ]. This option effectively abolishes the risk of post-operative cholangitis, although has a higher revision rate for leaks and obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Little has changed in the surgical technique of HPE since Kasai’s initial descriptions. Alternative techniques, such as drainage using the gallbladder, have been explored but were determined to have limited application …”
Section: Introductionmentioning
confidence: 99%
“…Alternative techniques, such as drainage using the gallbladder, have been explored but were determined to have limited application. 4 The rate of survival with native liver after a BED treatment is 37.9% to 40% after 5 years and decreases to 25% to 32.1% after 15 years, even at experienced centers and despite considerable efforts to improve the long-term outcomes. [5][6][7] Mortality occurs secondary to progressive hepatic injury, which leads to cirrhosis and end-stage liver disease that eventually require LT in most patients.…”
mentioning
confidence: 98%